Potential iriadiation of Asam Keumamah as an emergency food alternative - Abdul Hadi; Wiqayatun Khazanah; Andriani Andriani; Ampera Miko; Husna Husna (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Emergency food is safe and highly nutritious processed food for disaster victims. It is hoped that the various food product assistants provided after the disaster will be able to meet the needs, but some of the food cannot be stored for a long time. This study aimed to determine the potential of irradiated Asam Keumamah as an alternative to emergency food. The experimental study used a completely randomized design to irradiate five doses of Asam Keumamah stored for 30 days. Asam Keumamah was processed in the Food Technology Laboratory, Nutrition Department of the Aceh Polytechnic, in 2022. Data were collected through laboratory examinations including irradiation, total bacteria, and proximate tests. Statistical analysis was performed using ANOVA, Kruskal-Wallis, and Duncan’s tests at 95% CI. The results showed that an irradiation dose of 0-20 kGy had no significant effect on the total bacteria and approximate levels of irradiated Asam Keumamah (p>0,05). Irradiation doses of 30, 40, and 50 kGy significantly affected the fat and carbohydrate levels in Asam Keumamah (p< 0,05). In conclusion, irradiated and vacuumed Asam Keumamah lasts longer; therefore, it can be recommended as an alternative post-disaster emergency food source.